Efficacy and Safety of Transcatheter vs. Surgical Aortic Valve Replacement in Low-to-Intermediate-Risk Patients: A Meta-Analysis - Lou, Yake; Gao, Yanan; Yu, Ying; Li, Yanli; Xi, Ziwei; Swe, Khaing Nyein Chan; Zhou, Yujie; Nie, Xiaomin; Liu, Wei (Frontiers in Cardiovascular Medicine, 2020)
Purpose: We aimed to investigate the efficacy and safety of transcatheter aortic-valve replacement (TAVR) versus surgical aortic valve replacement (SAVR) for low- intermediate surgical risk patients. Methods: PubMed, Cochrane Library, and Embase databases were searched to identify potential references. Only randomized controlled trials (RCTs) or observational studies using propensity score matching were eligible for screening. The primary endpoint was all-cause death. The secondary outcomes were bleeding, stroke, myocardial infarction (MI) and other complications of aortic-valve replacement. In addition, we performed subgroup analysis based on surgical risk and study type. Results: Eight RCTs and 13 observational studies covering 12467 patients were included in the current meta-analysis. For patients with low-surgical risk, compared with SAVR, TAVR was found to be associated with a lower mortality at a follow-up period of 1-year (odds ratio, OR: 0.66, 95%CI: [0.46, 0.96], P=0.03). This benefit disappeared when the follow-up was extended to 2-year (OR: 0.89, 95% CI: [0.61, 1.30], P=0.56). For patients with intermediate-surgical risk, TAVR showed to have similar mortality with SAVR regardless of follow-up period (30-day, 1-year or 2-year). TAVR could reduce the incidence of bleeding, AF, AKI. For complications, such as MI and stroke, TAVR exhibited to have similar safety with SAVR. However, TAVR was found to be associated with a higher incidence of reintervention, major vascular complication, paravalvular leak, and PPI. Conclusion: For patients with low to intermediate surgical risk of AVR, TAVR have at least equal clinical effect as SAVR at 2 years after procedure.